2000
DOI: 10.1211/0022357001774930
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-ulcerogenic Effect of an Alkaloidal Fraction from Mikania cordata on Diclofenac Sodium-induced Gastrointestinal Lesions in Rats

Abstract: A decoction of Mikania cordata (Compositae) is commonly used for the treatment of gastric ulcer in the Rajbari district of Bangladesh. We have evaluated the anti-ulcerogenic effect of the alkaloidal fraction from the whole plant of M. cordata on diclofenac sodium-induced gastrointestinal lesion in rats. Long Evan's rats were divided into five groups. The control group was kept undisturbed. The vehicle group received vehicle after a 48-h fast. The diclofenac group received diclofenac sodium suspension (80 mg kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…In the study realized by Paul et al (2000) the alkaloid fraction obtained from an ethanolic extract of leaves of Mikania cordata (dose 50 mg/kg) exhibited antiulcer activity (in vivo) in gastric erosions induced by diclofenac sodium in rats Long Evans. Mosaddik & Alam (2000) carried out a similar study to evaluate the role of alkaloids fraction in gastric erosions induced by diclofenac sodium in rats Long Evans and found that in the alkaloidal-administered group (50 mg/ kg) the ulcer index of the stomach (0.268±0.0346) and of the duodenum (0.050±0.0129) were significantly lower than the diclofenac-only administered group (0,691±0,0184 and 0.093±0.0346, respectively). Thus, bioactive principles of M. cordata have proved antiulcerogenic effects.…”
Section: Activity In the Digestive Systemmentioning
confidence: 99%
“…In the study realized by Paul et al (2000) the alkaloid fraction obtained from an ethanolic extract of leaves of Mikania cordata (dose 50 mg/kg) exhibited antiulcer activity (in vivo) in gastric erosions induced by diclofenac sodium in rats Long Evans. Mosaddik & Alam (2000) carried out a similar study to evaluate the role of alkaloids fraction in gastric erosions induced by diclofenac sodium in rats Long Evans and found that in the alkaloidal-administered group (50 mg/ kg) the ulcer index of the stomach (0.268±0.0346) and of the duodenum (0.050±0.0129) were significantly lower than the diclofenac-only administered group (0,691±0,0184 and 0.093±0.0346, respectively). Thus, bioactive principles of M. cordata have proved antiulcerogenic effects.…”
Section: Activity In the Digestive Systemmentioning
confidence: 99%
“…Three deterpenic acids known as kaurenic acid, butyryloxykaurenic acid and benzoyloxykaurenic acid, stigmasterol and betasitosterin have also been isolated from this plant [4] . The plant is reported to have psychopharmacological and neuropharmacological properties; antimicrobial, antiinflammatory, antipyretic, ulcerprotective, anticarcinogenic activities [5][6][7][8] . But still no scientific and methodical investigation has so far been reported in literature regarding its analgesic and antioxidant action.…”
Section: Introductionmentioning
confidence: 99%
“…It is popularly known as "guaco" and possess pharmacological properties for treating the airways [1,2] . M. laevigata also possesses antimicrobial, [3] inflammatory, bronchodilator, antispasmodic, antirheumatic and antiulcerant activities [4,5] .…”
Section: Introductionmentioning
confidence: 99%